PAX‐FOXO1 fusion status drives unfavorable outcome for children with rhabdomyosarcoma: A children's oncology group report. Issue 9 (22nd March 2013) - Skapek, Stephen X.; Anderson, James; Barr, Frederic G.; Bridge, Julia A.; Gastier‐Foster, Julie M.; Parham, David M.; Rudzinski, Erin R.; Triche, Timothy; Hawkins, Douglas S.
Abstract Background Rhabdomyosarcoma (RMS) is divided into two major histological subtypes: alveolar (ARMS) and embryonal (ERMS), with most ARMS expressing one of two oncogenic genes fusing PAX3 or PAX7 with FOXO1 (P3F and P7F, respectively). The Children's Oncology Group (COG) carried out a multi‐institutional clinical trial to evaluate the prognostic value of PAX‐FOXO1 fusion status. Methods Study participants were treated on COG protocol D9803 for intermediate risk ARMS or ERMS using multi‐agent chemotherapy, radiotherapy, and surgery. Central diagnostic pathology review and molecular testing for fusion genes were carried out on prospectively collected specimens. Event‐free (EFS) and overall survival (OS) at 5 years were correlated with histological subtype and PAX‐FOXO1 status. Results Of 616 eligible D9803 enrollees, 434 cases had adequate clinical, molecular, and pathology data for definitive classification as ERMS, ARMS P3F+ or P7F+, or ARMSn (without detectable fusion). EFS was worse for those with ARMS P3F+ (54%) and P7F+ (65%) than those with ERMS (77%; P < 0.001). EFS for ARMSn and ERMS were not statistically different (90% vs. 77%, P = 0.15). ARMS P3F+ had poorer OS (64%) than ARMS P7F+ (87%), ARMSn (89%), and ERMS (82%; P = 0.006). Conclusions ARMSn has an outcome similar to ERMS and superior EFS compared to ARMS with either P3F or P7F, when given therapy designed for children with intermediate risk RMS. This prospective analysis supports incorporation of PAX‐FOXO1 fusion status into risk stratification and treatment allocation. Pediatr Blood Cancer 2013;60:1411–1417. © 2013 Wiley Periodicals, Inc.